Overcoming water scarcity and quality constraints: Water for Food Production - Rosegrant, Mark W.; Cai, Ximing (International Food Policy Research Institute, 2001)
Water for agriculture is critical for food security. However, water for irrigation may be threatened by rapidly increasing nonagricultural uses in industry, households, and the environment.